"Stain in life": The meaning of urinary incontinence in the context of Muslim postmenopausal women through hermeneutic phenomenology. Issue 3 (May 2015) - Hamid, Tengku Aizan; Pakgohar, Minoo; Ibrahim, Rahimah; Dastjerdi, Marzieh Vahid
Highlights UI was an obstacle to go to Hajj in Mecca for Iranian Muslim postmenopausal women. "Loosing desire to live with UI" was a unique meaning for the Persian culture. Advising to seek treatment will prevent UI's detrimental effects in life.